Exploring Cultural Disengagement: The Example of Chile. (December 2017) - Gayo, Modesto
Research on cultural capital has been very attentive to cultural participation. In numerous explorations of the social basis of participatory practices, a division between cultural engagement and disengagement has been frequently observed. In accordance with Bourdieu's seminal work on taste, that divide has been predominantly associated with social class issues. But research has only weakly explored the rationale behind people's behaviours in this regard. This article explores rationales for non-participation and reaches significant conclusions about these. First, non-participatory practices are very much spread across the social structure, and they are associated with different reasons (disliking, lack of time, money, information, habits, and access to venues). Second, the reasons provided by survey interviewees are affected differently by income levels, age and the size of the places people live in, amongst other important variables. Third, even though the effect of those variables on the reasons changes according to the legitimacy of the activities in which interviewees do not take part in, differences related to the status of the activities are less significant than similarities. I use data from Chile, collected in 2012, and the findings are linked to those of previous analyses undertaken in other countries.